Incidence of Type 1 diabetes and factors associated with presence and severity of ketoacidosis at onset in children - Tumini, Stefano; Baki, Salwa; Kosteria, Ioanna; Di Giuseppe, Italo; Levantini, Gabriella (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To assess the incidence of Type 1 Diabetes Mellitus (T1DM) during the period 2012-2017, the frequency and severity of ketoacidosis (DKA) at diabetes onset, and the factors associated with DKA in children and adolescents younger than 18 years old in the Abruzzo region, Italy.Methods: All incident cases of T1DM (0-17 years old) diagnosed between January 2012 and December 2017 were included. Data about the patients were obtained from two independent sources; insulin prescriptions and medical records. Clinical data at diabetes onset, as well as demographic and non-demographic data, including center of first hospitalization, distance to regional reference center and number of pediatricians (per 1000 residents younger than 18 years) were collected and evaluated.Results: During 2012-2017 period, 177 patients were diagnosed with T1DM. In 2012, T1DM incidence was 15.6 per 100,000/year; in 2013, 16.4 per 100,000/year; in 2014, 11.6 per 100,000/year; in 2015, 14.2 per 100,000/year; in 2016, 16.2 per 100,000/year and in 2017, 12.2 per 100,000/year. DKA was present in 29.3% of patients, 6.9% with severe DKA. The DKA presence was correlated to age (p